An analysis of the impact of affirmative action programs on self-employment in the construction industry - David G. Blanchflower; Jon Wainwright (Institute for the Study of Labor (IZA), 2005)
The main findings of this paper are that despite the existence of various affirmative action programs designed to improve the position of women and minorities in public construction, little has changed in the last twenty five years. We present evidence showing that where race conscious affirmative action programs exist they appear to generate significant improvements: when these programs are removed or replaced with race-neutral programs the utilization of minorities and women in public construction declines rapidly. We show that the programs have not helped minorities to become self-employed or to raise their earnings over the period 1979-2004, using data from the Current Population Survey and the Census, but have improved the position of white females. There has been a growth in incorporated self-employment rates of white women in construction such that currently their rate is significantly higher than that of white men. The data are suggestive of the possibility that some of these companies are 'fronts' which are actually run by their white male spouses or sons to take advantage of the affirmative action programs.
Keywords: J70; 330; discrimination; Arbeitsmarktdiskriminierung; Wirkungsanalyse; Bauwirtschaft; Selbstständige; USA